Environmental protection by ICAO : an assessment of the legal framework towards measures to reduce green house gas emissions in the international civil aviation sector - Hobe, Stephan (University of Pretoria, 2019)
Mini Dissertation (LLM)--Universiity of Pretoria, 2018.